2022
DOI: 10.1002/jhbp.1256
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of the JSHBPS nomogram for patients with colorectal liver metastases who underwent hepatic resection in the recent era ‐ a nationwide survey in Japan

Abstract: Background The Japanese Society of Hepato‐Biliary‐Pancreatic Surgery (JSHBPS) nomogram was developed to predict disease‐free survival in patients with colorectal liver metastases (CRLM) undergoing upfront hepatectomy. However, the utility of the nomogram in patients with resected CRLM remains unknown in the current situation in which treatment strategies are changing with advances in drugs. Methods Patients in the initial nomogram cohort (n = 727) and validation cohort (n = 2225) were divided into the upfront … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…23 The use of preoperative chemotherapy has increased in patients with CRLM. 24 In our study, RAS mutation status was not associated with the use of preoperative chemotherapy, and 29 patients with wild-type RAS received preoperative anti-EGFR antibody. Patients with RAS mutations do not respond to treatment with anti-EGFR antibodies 25 ; however, the use of anti-EGFR antibodies in patients with wild-type RAS may have affected our results.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…23 The use of preoperative chemotherapy has increased in patients with CRLM. 24 In our study, RAS mutation status was not associated with the use of preoperative chemotherapy, and 29 patients with wild-type RAS received preoperative anti-EGFR antibody. Patients with RAS mutations do not respond to treatment with anti-EGFR antibodies 25 ; however, the use of anti-EGFR antibodies in patients with wild-type RAS may have affected our results.…”
Section: Discussionmentioning
confidence: 59%
“…The use of preoperative chemotherapy has increased in patients with CRLM 24 . In our study, RAS mutation status was not associated with the use of preoperative chemotherapy, and 29 patients with wild‐type RAS received preoperative anti‐EGFR antibody.…”
Section: Discussionmentioning
confidence: 60%
“…11 We recently performed a validation study in 1756 patients with CRLM who underwent upfront hepatectomy between 2005 and 2007 after introduction of modern chemotherapy in Japan. 16 In the validation cohort, the proportions of patients with a 5-point increase in the Beppu score of the five groups were compared with those in the initial nomogram cohort (Supporting Information: Figure S1). The ratio of patients with Beppu scores ≥11 to all patients decreased, perhaps because of the increased number of patients treated with liver resection following preoperative chemotherapy.…”
Section: Beppu Scorementioning
confidence: 99%
“…Furthermore, in 2022, a validation study of the nomogram proved that this score had sufficient discriminatory power in the modern chemotherapy era. 16 Preoperative and postoperative chemotherapy alone or in combination have been attempted for patients with CRLM to decrease recurrences and improve long-term outcomes. [17][18][19][20][21][22][23][24][25][26] Some randomized controlled studies have shown significantly improved DFS or progression-free survival, but not overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation